2014
DOI: 10.1051/mfreview/2014003
|View full text |Cite
|
Sign up to set email alerts
|

Punching process including thickening of hole edge for improvement of fatigue strength of ultra-high strength steel sheet

Abstract: -A punching process including thickening of a hole edge of an ultra-high strength steel sheet with a taper punch and step die was developed to improve fatigue strength of the punched sheet. In this process, the sheet was punched by the bottom of the punch, and subsequently the hole edge was thickened by the taper of the punch and the corner step of the die. The taper angle of the punch and the step height of the die were optimised to increase the amount of thickening. The quality of the sheared edge for the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…With regard to the presence of residual compression stress, Yibo et al 29 reported the use of ultrasonic cavitation in stainless steel alloys, which increased surface roughness while at the same time generating residual compression stress that increases microhardness and resistance to cyclic fatigue. Moreover, Kadarno et al 30 reported a mechanical micro-punching process on stainless steel sheets that resulted in a regular plastic deformation surface that increased resistance to cyclic fatigue. The same authors mentioned that residual compression forces are responsible for this greater resistance to cyclic fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the presence of residual compression stress, Yibo et al 29 reported the use of ultrasonic cavitation in stainless steel alloys, which increased surface roughness while at the same time generating residual compression stress that increases microhardness and resistance to cyclic fatigue. Moreover, Kadarno et al 30 reported a mechanical micro-punching process on stainless steel sheets that resulted in a regular plastic deformation surface that increased resistance to cyclic fatigue. The same authors mentioned that residual compression forces are responsible for this greater resistance to cyclic fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum damage occurs in preparing a hole by punching route because material failure by shear happens at the shear edge. 10 Branagan et al 11 reported that all tested alloys show the highest HER values for EDM cut and milled holes and the lowest for the punched hole. Normally, shear failure happens during the hole preparation in sheet metal by punching, and as a result, maximum damage takes place at the shear edge.…”
Section: Introductionmentioning
confidence: 98%
“…Normally, shear failure happens during the hole preparation in sheet metal by punching, and as a result, maximum damage takes place at the shear edge. 10 Several researchers 1,1218 observed voids and cracks near the shear edge for various metals. Wechsuwanmanee et al 19 studied the effect of surface roughness of DP1000 steel on HER.…”
Section: Introductionmentioning
confidence: 99%
“…Jaafar et al [29] introduced automatic centering with a moving die into the slight clearance punching process in order to simplify setting of the punch having a small round corner and prevented the occurrence of delayed cracking for punched 1.5 GPa sheets by the compressive residual stress. On the other hand, Mori et al [30] ironed a hole of a punched ultra-high strength steel sheet with a taper punch in order to smooth the sheared edge, and Kadarno et al [31] developed a punching process including thickening around a hole with a taper punch and step die. In these punching processes, the tensile residual stress is considerably reduced by applying large shear deformation to the sheared edge under a high contact pressure, and thus, the risk level of delayed cracking becomes low.…”
Section: Introductionmentioning
confidence: 99%